Pengaruh Servant Leadership, Cultural Intelligence, Dan Emotional Intelligence Terhadap Job Performance Pada Karyawan CV dan Cell Nganjuk - Mafrukhah, Inavatul; Siwi Agustina, Tri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This study aims to test and analyze the effect of servant leadership, cultural intelligence, and emotional intelligence on job performance of CV. Dan Cell Nganjuk employees. This research uses a quantitative approach. Determination of the sample size using the slovin formula with a margin of error of 10% so that a sample of 74 respondents was obtained. The sampling technique used a simple random sampling technique. The data collection method uses a questionnaire with the help of SPSS 25 software as a data analysis tool. The results showed: (1) servant leadership has a positive and significant effect on job performance, (2) cultural intelligence has a positive and significant effect on job performance, (3) emotional intelligence has a positive and significant effect on job performance.